Improved safety of biologic therapy for rheumatoid arthritis over the 8-year period since implementation in Japan: long-term results from a multicenter observational cohort study. Issue 4 (April 2016) - Kojima, Toshihisa; Takahashi, Nobunori; Funahashi, Koji; Asai, Shuji; Terabe, Kenya; Kaneko, Atsushi; Hirano, Yuji; Hayashi, Masatoshi; Miyake, Hiroyuki; Oguchi, Takeshi; Takagi, Hideki; Kanayama, Yasuhide; et al.
Abstract This study aimed to compare the long-term safety of biologics by initiation year of treatment in patients with rheumatoid arthritis (RA) in Japan. RA patients who started their first biologics including infliximab, etanercept, adalimumab, and tocilizumab between 2003 and 2008 were identified in the Tsurumai Biologics Communication Registry (TBCR), multicenter observational cohort, and followed for 2 years or until discontinuation of the drugs. We identified baseline predictors for adverse events (AEs) resulting in discontinuation of the first TNFI using Cox proportional hazards regression analysis. A total of 874 cases (1, 340 person-years) were observed. During the observation period, 96 AEs (4.7 events/100 person-years) occurred. From 2003 to 2008, there were significant changes in disease duration, Steinbrocker stage, and disease activity in those aged ≤64 years with no increase of incidence of AEs, whereas those aged >64 years had no significant changes in these variables. In the later initiation year of treatment with biologics, the fewer AEs were observed (log-rank, p  = 0.017, 2008 vs. 2003–2005). Multivariate analysis showed that the initiation year significantly impacted the incidence of AEs 6 months into the observation period [initiation at 2008 (vs. 2003–2005): OR: 0.30, 95 % CI: (0.14–0.68)] after adjusting for variables at baseline. The decrease of AEs in the later initiation year was evident in those aged >64 years. The safety of biologic therapy improved over the course of the 8 years from its implementation in Japan.